Toksisitas Campuran Ekstrak Daun Sirsak (Annona muricata L.) dan Daun Jeruk Purut (Citrus hystrix) Terhadap Mortalitas Larva Nyamuk Aedes aegypti L. dan Pemanfaatannya sebagai Booklet - Nabila Salsa Violina (Fakultas Keguruan dan Ilmu Pendidikan, 2026)
Dengue Hemorrhagic Fever (DHF) is a global health problem primarily transmitted by the bite of the Aedes aegypti L. mosquito. Vector eradication using chemicals, which is frequently conducted today, has proven to have negative impacts on the environment and trigger insect resistance. An alternative to DHF vector eradication is the use of natural larvicides. Plants with the potential to serve as natural larvicides include soursop leaves (Annona muricata L.) and kaffir lime leaves (Citrus hystrix). Both leaves contain active compounds that can be utilized as natural larvicides. This study aimed to analyze the LC50 value of a mixture of soursop and kaffir lime leaf extracts on the mortality of Aedes aegypti L. larvae within a 24-hour exposure time. This research employed a quantitative laboratory experimental method, followed by probit analysis and the development of an informational booklet. The larvae used in each treatment were 20 Aedes aegypti L. instar III until instar IV. The experiment was conducted with four replications using a concentration series of 25 ppm, 500 ppm, 1000 ppm, and 1500 ppm, as well as positive and negative control groups. Based on the probit analysis, the LC50 of the mixture of soursop and kaffir lime leaf extracts against Aedes aegypti L. larvae within a 24-hour was 724.853 ppm, with a lower bound of 600.461 ppm and an upper bound of 832.965 ppm. The booklet validation results obtained an average score of 88%, meeting the criteria of being feasible for use as a source of information for the community.
:: Finalisasi file repositori 21 Juli 2026_Kurnadi
Keywords: Aedes aegypti L.; larvacide